A systematic review and meta-analysis of the sinus tarsi and extended lateral approach in the operative treatment of displaced intra-articular calcaneal fractures. Issue 5 (October 2019) - Nosewicz, Tomasz L.; Dingemans, Siem A.; Backes, Manouk; Luitse, Jan S.K.; Goslings, J. Carel; Schepers, Tim
Highlights: Systematic review and meta-analysis according to the PRISMA guidelines. Two approaches in calcaneal fracture treatment were investigated. The sinus tarsi approach (STA) and the extended lateral approach (ELA). The less invasive STA showed significantly less wound healing complications. Abstract: Background: The optimal surgical approach for displaced intra-articular calcaneal fractures (DIACF) is subject of debate. The primary aim of this systematic review and meta-analysis was to assess wound-healing complications following the sinus tarsi approach (STA) compared to the extended lateral approach (ELA). Secondary aims were to assess time to surgery, operative time, calcaneal anatomy restoration, functional outcome, implant removal and injury to the peroneal tendons and sural nerve. Methods: MEDLINE, EMBASE and Cochrane databases were searched for clinical studies comparing the STA and the ELA (until September 2017). Results: Nine studies were included (two randomized controlled trials; seven comparative studies). 326 patients (331 fractures) were treated by the STA and 383 patients (390 fractures) by ELA. Ninety-nine per cent were Sanders type II/III fractures. Wound healing complications in the STA and ELA occurred in 11/331 and 82/390 fractures, respectively. Weighted means were 4.9% and 24.9%, respectively. Meta-analysis showed significantly less wound healing complications in the STA compared to ELA (risk ratio 0.20; 95% CI 0.11–0.36; P < 0.00001; I 2  = 0%). In general, time to surgery and operative time were shorter in the STA. Meta-analysis was not possible due to heterogeneity between studies. No differences were found in remaining secondary outcomes. Conclusions: The STA is associated with significantly less wound healing complications. With similar functional outcome and calcaneal anatomy restoration, the STA may be the preferred approach in the operative treatment of Sanders type II/III DIACF.